How to read a book - Adler, Mortimer J. (Mortimer Jerome), 1902-2001; Van Doren, Charles, 1926-2019 (New York : Simon and Schuster, 1972)
Investigates the art of reading by examining each aspect of reading, problems encountered, and tells how to combat them.
The dimensions of reading: The activity and art of reading ; The levels of reading ; The first level of reading : elementary reading ; The second level of reading: inspectional reading ; How to be a demanding reader -- The third level of reading: Analytical reading: pigeonholing a book ; X-raying a book ; Coming to terms with an author ; Determining an author's message ; Criticizing a book fairly ; Agreeing or disagreeing with an author ; Aids to reading -- Approaches to different kinds of reading matter: How to read practical books ; How to read imaginative literature ; Suggestions for reading stories, plays, and poems ; How to read history ; How to read science and mathematics ; How to read philosophy ; How to read social science -- The ultimate goals of reading: The fourth level of reading: syntopical reading ; Reading and the growth of the mind.
Includes bibliographical references (pages 347-362) and index.
Keywords: Reading